The Role of Christian Religious Education Teachers in Improving Student Learning Achievement at Bhakti Insani Vocational High School in Bogor City - Yosina Hitus; Ayu Sutrisna (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2024)
PAK teachers have the responsibility to educate and improve students' learning achievements. Efforts to improve student learning achievement are not an easy task for a teacher because often students cannot achieve learning achievements as expected by teachers and schools. The decline in student learning achievement is caused by students not understanding the teacher's explanations, monotonous and less creative learning methods, low learning motivation, spending more time playing games, and lack of attention from parents/family. This research aims to determine the role of Christian Religious Education teachers in improving the learning achievement of students at Bhakti Insani Vocational School, Bogor City. The research methodology used is descriptive qualitative with a literature study, observation and interview approach. To achieve learning achievement, students need to receive direction, guidance, motivation, creative learning methods, and attention from Christian Religious Education teachers. That is why, good collaboration between teachers, schools, and parents/families helps students improve their learning achievements.